Transforming Health Professions Education for Universal Health Coverage: Challenges and Recommendations for Low-Resource Countries (Mugda Medical College Journal, 2023)
Health workforce challenge persists as a critical issue in achieving universal health coverage (UHC) goals globally, especially in resource-poor countries. Evidence shows that health professions education and training is primarily clinical and curricular; however, it is somewhat deviated from the needs of the health system. In low-resource countries like Bangladesh, in the context of limited financial realities, to achieve global health goals and maximize opportunities for employment and economic development a paradigm shift is needed in health professions education, workforce development and healthcare services of the country from its primary to the tertiary level of health care respectively. There is a critical need to shift towards fair, equitable, need-based employment policy that is compatible with the overall growth of the health economy, and that acknowledges the role of both public and private sector in education and training. This review paper tried to emphasize the importance and implications of a paradigm shift in the sector. It argues the need for a 21st century framework for health professions education. This framework should represent a more satisfactory interface between supply and demand for health professionals, in line with the current need to meet the targets of universal health coverage, rational employment in healthy sector and economic development.Mugda Med Coll J. 2022; 5(2): 98-103